THE EFFECT OF PERSONAL SELLING, DIGITAL MARKETING, BRAND IMAGE, AND LOCATION ON THE DECISION TO BECOME A CUSTOMER OF PT BANK SYARIAH INDONESIA KCP MALANG KAWI - Khumairoh, Fina Al; Hasan, Irmayanti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study sought to ascertain how personal selling, digital marketing, brand image, and location influenced consumers' decisions to patronize PT Bank Syariah Indonesia KCP Malang Kawi. Accidental and purposeful sampling techniques are utilized in the quantitative research methodology. The information used in this study came from questionnaire responses given to PT Bank Syariah Indonesia KCP Malang Kawi clients, who served as the study's research subjects. 144 respondents made up the samples used in this study. Multiple linear regression analysis was used in this investigation. Studies suggest that location, brand image, digital marketing, and partial personal selling have a considerable beneficial impact on a consumer's decision to use PT Bank Syariah Indonesia KCP Malang Kawi. Likewise, personal selling, digital marketing, brand image, and location all work in concert (simultaneously) to significantly affect a person's decision to use PT Bank Syariah Indonesia KCP Malang Kawi.